DIGITAL BRANDING UNTUK SEKOLAH ISLAM: MENINGKATKAN CITRA DAN DAYA TARIK PESERTA DIDIK - Moh. Holidi; Hafidatun Nabila; Aminullah Aminullah; Uryatul Hikmah; Yusril Ihza Saputra; Akmal Mundiri (STKIP Pesisir Selatan, 2026)
This study aims to analyze digital branding strategies in Islamic schools in improving the image of the institution and attracting new students. The research focus includes the effectiveness of social media, websites, and digital content in shaping the public's positive perception of schools. The research uses a descriptive qualitative approach with case studies in Islamic schools that have implemented active digital branding. Data was collected through in-depth interviews with marketing teams, observation of social media accounts, and digital content analysis. The analysis was carried out using thematic coding techniques to identify strategic patterns, competitive advantages, and their impact on student engagement. Results show that the use of consistent, interactive, and informative digital content increases public awareness, strengthens the school's reputation, and encourages increased enrollment. Storytelling strategies based on Islamic values and academic achievement have proven effective in building a positive image. These findings provide practical guidance for Islamic education managers to design a structured digital branding strategy, increase student attractiveness, and strengthen the institution's position in the digital era. The results of the research are also the basis for the development of sustainable digital marketing practices in faith-based educational institutions.